Evaluation of factors, associated with defaulting routine immunization in children - Chinnappa, Gayathri Devi; Reddy, Chikkanarasa P. S.; Sabapathy, Sarala; Varghese, Deepthy Alice (International Journal of Contemporary Pediatrics, 2020)
Background: India was one of the first countries to adopt the World Health Organization’s Expanded Programme of Immunization (EPI). The program started globally in 1974 and was initiated in India in 1978. Immunization is considered to be one of the most important cost-effective and a powerful public health intervention. Achieving maximum coverage, however, has been a challenge due to many reasons, including high rates of defaulters from the program. The term ªdefaulterº is used to refer a child who misses the scheduled vaccinations for any reason. The objective of this study was to explore the reasons behind defaulting from the routine immunization program. Methods: A study was conducted in Bowring and Lady Curzon Hospital, Bangalore between January 2012 and December 2012. A total of sixty six children’s’ details were gathered from mothers of defaulted children. Children below 5 years attending OPD were included in the study. Children above 5 years and inpatients were excluded. Observations and review of relevant documents was done. Results: Of the 66 children, in our study, males were more than females. Children in the age group of 2 years to 5 years were 17(25%) as compared to those between 1 to 2 years. Mothers were more literate than fathers. Muslim children had the best immunization coverage. The main determinant of defaulting was lack of knowledge and awareness regarding immunization by the mothers (21/31%) followed by sickness in children (11/16%), causing them to default immunization schedules Conclusions: The main reason for defaulting from the immunization program was lack of awareness, regarding immunization by mothers in the community.